2010
DOI: 10.1093/tropej/fmq060
|View full text |Cite
|
Sign up to set email alerts
|

HealthCare-associated Infections in a Neonatal Intensive Care Unit in Turkey in 2008: Incidence and Risk Factors, A Prospective Study

Abstract: In this study, we have prospectively recorded healthcare-associated infections (HAIs) in NICU and found incidence density as 18 infections per 1000 patient days. Of the infections, 51.3% was bacteriemia (BSI), and 45.1% was ventilator-associated pneumonia (VAP). Gram-negative microorganisms were predominant in VAP and Staphylococcus epidermidis was the leading microorganism (53.0% of BSIs) in BSIs. Multivariate logistic regression analysis showed the importance of hood O(2) use in days (RR: 1.3) and total pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 29 publications
3
18
2
2
Order By: Relevance
“…In our study, the rate of cathether related bloodstream infection was found to be 9,6:1000 days. It was noted that this rate was lower than the rate found in the study performed in our country by Yap›c›o¤lu et al (18). It was found that nasocomial infection was observed 2,46 fold more frequently when cathether was used in term babies and 3,1 fold more frequently when cathether was used in preterm babies.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…In our study, the rate of cathether related bloodstream infection was found to be 9,6:1000 days. It was noted that this rate was lower than the rate found in the study performed in our country by Yap›c›o¤lu et al (18). It was found that nasocomial infection was observed 2,46 fold more frequently when cathether was used in term babies and 3,1 fold more frequently when cathether was used in preterm babies.…”
Section: Discussioncontrasting
confidence: 53%
“…In the NNIS (National Nasocomial Infections Surveillance in USA) study, the rate of bloodtream infection caused by use of cathether was found to be 3.5-9.1: 1000 days (19). In the prospective studies performed by Perlman et al (20) in two NICU's, In the USA National Hospital study, the rate of cathether related bloodstream infection was reported to be 7.4-16.1: 1000 days in newborns between 1000 and 2500g for 90th percentile (18). In our study, the rate of cathether related bloodstream infection was found to be 9,6:1000 days.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations